Socio-Economic Status Of Goat Farmers In Southern Agro-Climatic Region Of Tamil Nadu - Kumar, S.Vasantha; Kumar, V.Ramesh Saravana; Muralidharan, J.; Murali, N.; Vasanthakumar, P. (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
A study was conducted to analyse the goat farming practices adopted by farmers under field conditions in southern agro-climatic region of Tamil Nadu. A total of 180 goat farmers were utilised for this study in Tirunelveli, Thoothukudi and Virudhunagar districts. Based on the agricultural land holding the goat farmers were categorised as landless, marginal, small and large land holders and they were 48.89, 33.89, 10.56 and 6.66 per cent, respectively with the mean land holding size of 1.50 ± 0.17 acres. Goat farmers preferred to live in nuclear family (78.33 per cent) than joint family (21.67 per cent). Majority of goat farmers in the study area were Hindus (91.11 per cent) and remaining (8.89 per cent) were Christians and they belonged to the backward class, scheduled class and most backward communities comprising 37.23, 34.44 and 28.33 per cent, respectively. Farmers had an average of 10.41 ± 0.46 years of experience in goat farming. The average annual income generated by the goat farmers in the study area was Rs. 53,160.16.
Keywords: Goat farming; Socio - economic status; Southern region; Tamil Nadu